Dissecting the neural circuitry of fear-induced appetite suppression - Shaw, Jessica (Neuron, 2021)
The circuit that links stress and fear to feeding behavior is poorly understood. In this issue of Neuron, Yang et al. detail a trisynaptic, cannabinoid-dependent circuit that underlies appetite suppression in response to a fearful stimulus and provide evidence of noradrenaline and glutamate co-transmission in locus coeruleus.